Impacts of STEM Professional Development on Teachers' Knowledge, Self-Efficacy, and Practice - Gardner, Kimberly; Glassmeyer, David; Worthy, Roneisha (Frontiers in Education, 2019)
Research frameworks outline key aspects of STEM (science, technology, engineering, mathematics) integration for teachers, but translating this research into productive changes in teachers’ classroom practices remains a challenge, particularly in schools without an emphasis on STEM integration. In this article, we detail how a STEM education descriptive framework was used to design and enact a year-long professional development with eight secondary teachers at non-STEM focused schools in Southeast USA. Using teacher self-efficacy scores on pre- and post-tests, self-reported STEM integration efforts, and other feedback, we saw productive changes in teachers’ classroom practices and self-efficacy. We conclude with how this STEM education descriptive framework can be helpful in designing effective professional development for teachers at non-STEM focused schools.